Frequency and Env determinants of HIV-1 subtype C strains from antiretroviral therapy-naive subjects that display incomplete inhibition by maraviroc. Issue 1 (December 2016) - Borm, Katharina; Jakobsen, Martin; Cashin, Kieran; Flynn, Jacqueline; Ellenberg, Paula; Ostergaard, Lars; Lee, Benhur; Churchill, Melissa; Roche, Michael; Gorry, Paul
Abstract Background Entry of human immunodeficiency virus type 1 (HIV-1) into cells involves the interaction of the viral gp120 envelope glycoproteins (Env) with cellular CD4 and a secondary coreceptor, which is typically one of the chemokine receptors CCR5 or CXCR4. CCR5-using (R5) HIV-1 strains that display reduced sensitivity to CCR5 antagonists can use antagonist-bound CCR5 for entry. In this study, we investigated whether naturally occurring gp120 alterations in HIV-1 subtype C (C-HIV) variants exist in antiretroviral therapy (ART)-naïve subjects that may influence their sensitivity to the CCR5 antagonist maraviroc (MVC). Results Using a longitudinal panel of 244 R5 Envs cloned from 20 ART-naïve subjects with progressive C-HIV infection, we show that 40% of subjects (n = 8) harbored viruses that displayed incomplete inhibition by MVC, as shown by plateau's of reduced maximal percent inhibitions (MPIs). Specifically, when pseudotyped onto luciferase reporter viruses, 16 Envs exhibited MPIs below 98% in NP2–CCR5 cells (range 79.7–97.3%), which were lower still in 293-Affinofile cells that were engineered to express high levels of CCR5 (range 15.8–72.5%). We further show that Envs exhibiting reduced MPIs to MVC utilized MVC-bound CCR5 less efficiently than MVC-free CCR5, which is consistent with the mechanism of resistance to CCR5 antagonists that can occur in patients failing therapy. Mutagenesis studies identified strain-specific mutations in the gp120 V3 loop that contributed to reduced MPIs to MVC. Conclusions The results of our study suggest that some ART-naïve subjects with C-HIV infection harbor HIV-1 with reduced MPIs to MVC, and demonstrate that the gp120 V3 loop region contributes to this phenotype.